France citizenship in the aftermath of 2015: officializing a two-tier system?. Issue 8 (17th November 2017) - Barras, Amélie
Abstract: Over the last decade, France has put in place a series of measures to reinforce laïcité and Republican values . While these notions have never clearly been defined, they have been used as a justification to scrutinize and interfere in the bodies, sensibilities and practices of 'Muslim' citizens. In the aftermath of the Charlie Hebdo attacks in January 2015 and the November 13th terrorist attacks that same year, these policies have become ever more important, and are buttressed by new 'extraordinary' measures, such as the 'State of Emergency'. This article explores these different measures, and analyzes their consequences for French citizens, especially citizens of Muslim faith. It also pays attention to political and legal strategies put forth by activists to denounce these recent shifts, and to propose a more inclusive and equal understanding of citizenship.